Generation of an induced pluripotent stem cell line (ZJULLi003-A) from a hypertrophic cardiomyopathy patient carrying MYH7/c.4384G > A mutation - Jingjun Zhou; Yaxun Sun; Hongkun Wang; Hao Wang; Fengfeng Guo; Xianzhen Chen; Tingyu Gong; Chenyang Jiang; Ping Liang (Stem Cell Research, 2022)
Hypertrophic cardiomyopathy (HCM) is an autosomal dominant inherited cardiovascular disease characterized by left ventricular hypertrophy and cardiomyocyte disarray. In this study, a skin biopsy was obtained from a HCM patient, who carried a missense mutation (c.4384G > A; p.E1462K) in the myosin heavy chain 7 (MYH7) gene. The skin fibroblasts were subsequently reprogrammed with a non-integrated Sendai viral method to generate a patient-specific induced pluripotent stem cell (iPSC) line. The generated iPSC line showed typical morphology and normal karyotype, expressed pluripotency markers, and was capable to differentiate into three germ layers.